Description of a new uniformly brown estuarine moray eel (Anguilliformes, Muraenidae) from the Central Indo-Pacific Ocean - Wen-Chien Huang; Yusuke Hibino; Rodulf Anthony Balisco; Te-Yu Liao (ZooKeys, 2024)
A new estuarine moray eel, Uropterygius hades sp. nov., is described based on 14 specimens from Japan, Taiwan, the Philippines, southern Indonesia, and Fiji. It is a small-bodied, slender, uniformly dark-brown moray separated from congeners within the U. concolor species complex. The new species can be distinguished from congeners by the anteriorly positioned small eyes (5.0–7.2% of head length), absence of branchial pores, and extended inner rows of teeth which reach the posterior end of the jaws. Uropterygius hades sp. nov. represents a rare species of moray eel that inhabits turbid estuarine environments, preferring soft, muddy substrates, and burrowing and hiding among rocks or in fallen mangrove leaves. Additionally, Uropterygius mactanensis Huang, Balisco, Evacitas & Liao, another species recently separated from the U. concolor species complex, is reported for the first time from Iriomote Island in the Ryukyu Archipelago based on two specimens; this new record expands the geographic range of U. mactanensis from the central Philippines to southern Japan.